Uji Aktivitas Antibakteri Ekstrak Etanol Kulit Buah Manggis (Garcinia Mangostana L) Terhadap Bakteri Escherichia Coli Atcc 11229 Dan Staphylococcus Aureus Atcc 6538 Secara In Vitro - Aziz, Mohamad Azwar; , dr. M. Amin Romas, DSMK; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background : Mangosteen rind (Garcinia mangostana l) is one of plant herbal simplicia have contain substance active discover good killed of bacterial like flavonoids, xanthone, tannin, terpenoid, and saponin. Mangosteen rind (Garcinia mangostana l) is one of plant that have a potency to use as a drugs. objective : The research purpose to find the inhbiting activity of the ethanol extract of mangosteen rind (Garcinia mangostana l) against the Escherichia coli and Staphylococcus aureus growth. Method : This study used laboratory experimental research design (true experimental) with post test only control group design method. The ethanol extract of mangosteen rind (Garcinia mangostana l) is tested by well method with concentration 5%, 10%, 20%, 40%, 60%, and 80% w/v. Wells is made on Muller Hinton germ growth media which is smeared by culture of Escherichia coli ATCC 11229 AND Staphylococcus aureus ATCC 6538 which has been standardized by Mc Farland. The ethanol extract of mangosteen rind (Garcinia mangostana l) drip in to the well with various concentration. It is incubated with a temperature of 370c for 24 hours and inhibition of zone radical is measured by Vernier caliper. Research results : The ethanol extract of mangosteen rind (Garcinia mangostana l) with concentration 5%, 10%, 20%, 40%, 60%, and 80% w/v, can inhibit the growth Staphylococcus aureus whit mean inhibition zone diameter is 10,6 mm, 12,6 mm, 14,8 mm, 15 mm, 15,8 mm, dan 16,8 mm and the velue of statistic Kurskall Wallis test 0,000. While Escherichia coli the extract of mangosteen rind can not inhibition zone and the velue of statistic Kurskall Wallis test unknown. Conclusion : The ethanol extract of mangosteen rind (Garcinia mangostana l) has antibacterial activity against Staphylococcus aureus ATCC 6538 in vitro